Comparative Chloroplast Genomics and Phylogenetic Analysis of Thuniopsis and Closely Related Genera within Coelogyninae (Orchidaceae) - Li, Lin; Wu, Qiuping; Fang, Lin; Wu, Kunlin; Li, Mingzhi; Zeng, Songjun (Frontiers in Genetics, 2022)
The genus Thuniopsis was recently proposed for a rare orchid species T. cleistogama formerly classified in the genus Thunia. The relationships between Thuniopsis and its related genera have not yet been conclusively resolved. Recognition of the genus provides a new perspective to illustrate the morphological diversity and plastome evolution within Coelogyninae. In this study, we sequenced and assembled complete chloroplast (cp) genomes for three accessions of Thuniopsis cleistogama and two accessions of Thunia alba. A total of 135 genes were annotated for each cp genome, including 89 protein-coding genes, 38 tRNA genes, and eight rRNA genes. The ENC-plot and neutrality plot analyses revealed that natural selection dominated over mutation pressure in their evolutionary process. Specially, we found that selection played a vital role in shaping the codon usage in Thunia alba cp genome. General characteristics of the cp genomes were further analyzed and compared with those published plastomes of four other related species. Despite the conserved organization and structure, the whole individual cp genome size ranged from 158,394 bp to 159,950 bp. In all the examined plastomes, sequences in the inverted repeat (IR) regions were more conserved than those in the small single copy (SSC) and large single copy (LSC) regions. However, close examination identified contraction and expansion of the IR/SSC boundary regions, which might be the main reason for the cp genome size variation. Our comparative analysis of the cp genomes revealed that single nucleotide polymorphisms (SNPs) and insertions/deletions (InDels) provided valuable information for identifying genetic variations within and among genera. Furthermore, sequence variations in the protein-coding regions were more conserved than those in the noncoding regions. We selected eight divergence hotspots with nucleotide sequence diversities (Pi values) higher than 0.08. Most of these polymorphisms were located in the intergenic regions. Phylogenomic analyses recovered largely congruent relationships among major clades and strongly supported the monophyly of Thuniopsis. The results obtained in this study can improve our understanding of the classification of this enigmatic genus. The cp genomic data presented here provide valuable insights into the phylogeny and evolutionary patterns of the Coelogyninae.